2014
DOI: 10.1007/s00464-014-3434-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripancreatic pseudoaneurysms: a management-based classification system

Abstract: Background Peripancreatic pseudoaneurysms can arise in a number of different clinical settings but are associated mostly with pancreatitis and pancreatobiliary surgery. The aim of this study is to review the current literature and to propose a management classification system based on the pathophysiological processes and the exact anatomical site of peripancreatic pseudoaneurysms.MethodsA systematic review of the literature from 1995 to 2012 was performed. Articles on studies describing peripancreatic pseudoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 40 publications
0
88
0
3
Order By: Relevance
“…(2,9,11,18) Gambiez et al (19) presented in his study that the majority of his patients were surgically treated and no signs of recurrent bleeding were present after definitive pancreatic surgery. He also concluded that angiographic methods might associate other severe complications such as necrosis of the duodenum or the development of spleen abscesses.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…(2,9,11,18) Gambiez et al (19) presented in his study that the majority of his patients were surgically treated and no signs of recurrent bleeding were present after definitive pancreatic surgery. He also concluded that angiographic methods might associate other severe complications such as necrosis of the duodenum or the development of spleen abscesses.…”
Section: Discussionmentioning
confidence: 95%
“…A single procedure of embolization or stenting has a high rate of failure and often several attempts are done in order to completely manage the aneurysm. (2) These specialized procedures are highly dependent on the endowment of the medical facility in which the patient is treated. Ideally for the patient is to receive treatment in an angio-surgical-setting under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations